RISK OF ENERGY COMPANIES - E. Kamchatova; A. Kostenko (Вестник университета, 2016)
The article presents a qualitative analysis of risks energy companies on the basis of their classification. The analysis of the main types of risk generation, transmission and retail companies and the impact of risks on the results of their activities. The result is a material that is used as a basis for further building the risk management system on the basis of their classification, ranking, and determining the extent of their impact on the operations of energy companies.